Organizational Communication and Pensioners’ Satisfaction: A Mediation Analysis of Trust in Monopolistic Public Service - Jaya, Ida; Rozzana, Mira; Gumay, Nanda Fathiyah (LPPM STIE KRAKATAU, 2025)
This study investigates the complex interplay between organizational communication, trust, and satisfaction among pensioners in the context of a mandatory public service. While trust is conventionally viewed as a key driver of satisfaction, this study explores whether this holds true for monopolistic institutions such as TASPEN in Indonesia. Using a quantitative explanatory design, data were collected from 78 pensioners [asumsikan jumlah sampel] at a provincial branch and analyzed using SEM-PLS (SmartPLS 3.0). The findings revealed a robust positive impact of organizational communication on both satisfaction and trust. However, surprisingly, trust does not significantly mediate or influence pensioners' satisfaction. This